Pengaruh Business Model Innovation, Erm Terhadap Kinerja Umkm Dengan Mediator Competitive Advantage - Yanni Octavio, F.X. Kurniawan Tjakrawala (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The research aims to obtain empirical evidence on the impact of business model innovation and enterprise risk management on SME performance with a competitive advantage as an intervening variable. This research used 95 samples of primary data using a questionnaire based on the method of purposive sampling. The respondents to this research are the owners and managers of SMEs on Java Island. This research utilizes SPSS version 21 and SmartPLS version 3.3.2 to perform data processing. The results obtained in this research are business model innovation and enterprise risk management have a significant and positive effect on SME performance when mediated partially by competitive advantage. The implications of this study are the need to understand the role of business model innovation, enterprise risk management, and competitive advantage that will improve SME performance.